2014
DOI: 10.1002/app.40436
|View full text |Cite
|
Sign up to set email alerts
|

Production and isolation of chitosan from Aspergillus terreus and application in tin(II) adsorption

Abstract: Fed‐batch fermentation was used for biomass and fungal chitosan production by Aspergillus terreus (BCRC 32068) grown in a potato dextrose agar medium. The polysaccharides were extracted by an alkali–acid treatment, and structural investigations by X‐ray diffraction, Fourier transform infrared analysis, and viscosity and thermal analysis were done. A high level of chitosan was extracted from A. terreus; this implied that it was feasible to produce chitosan from industrial waste mycelia. Fungal chitosan derived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 22 publications
0
2
0
1
Order By: Relevance
“…The current study established the biocidal potential of chitosan against R. stolonifer and reported that the application of this natural fungicide can enhance the shelf life of tomato fruits. Due to its non-toxicity, biodergardable, and organic nature chitosan derivatives have been successfully used for the management of fungal diseases and enhancing fruit self-life (Cheng et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The current study established the biocidal potential of chitosan against R. stolonifer and reported that the application of this natural fungicide can enhance the shelf life of tomato fruits. Due to its non-toxicity, biodergardable, and organic nature chitosan derivatives have been successfully used for the management of fungal diseases and enhancing fruit self-life (Cheng et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, fungi have been deeply investigated for industrial applications as bio-based materials [ [14] , [15] , [16] ]. The extraction of chitin from non-animal sources as fungi is possible [ [17] , [18] , [19] ] and it can be particularly attractive because it has no impact on animals [ 20 ]. Few cultivated edible species of fungi were already tested as chitin sources, with the aim of recycling waste parts.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, fungi have been deeply investigated for industrial applications as bio-based materials [14][15][16]. The extraction of chitin from non-animal sources as fungi is possible [17][18][19] and it can be particularly attractive because it has no impact on animals [20]. Few cultivated edible species of fungi were already tested as chitin sources, with the aim of recycling waste parts.…”
Section: Introductionmentioning
confidence: 99%